Response to “Methodological Sensitivities to Latent Class Analysis of Long-Term Criminal Trajectories” - Nagin, Daniel (Journal of quantitative criminology, 2004)
This response to “Methodological Sensitivities to Latent Class Analysis of Long-Term Criminal Trajectories” is intended to make three key points: (1) the data sensitivities that are explored in that paper are examples of two generic data problems that transcend the specific methodology used to analyze longitudinal data, (2) while real sensitivities are identified, the overall stability of results is also noteworthy, and (3) the groups must be understood to be approximations.